2021
DOI: 10.1002/slct.202102781
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Phenothiazine‐Benzothiadiazine‐1,1‐dioxide Hybrid Organic Material for OLED Applications

Abstract: In this study, yellow thermally activated delayed fluorescence (TADF) emitter PTZ-SA has been designed and synthesized by incorporating phenothiazine as donor and benzothiadiazine-1,1-dioxide as an acceptor. The molecule is also screened for aggregation induced emission in THF/Water system. PTZ-SA shows exceptionally high glass transition temperature (T g ) of 188 °C which clearly highlights good thermal stability of the material. The energy gap (ΔE ST ) between singlet (S1) and triplet (T1) excitons is suffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In recent years the venerable electron-rich phenothiazine heterocycles have stimulated increasing scientic interest and have been successfully established in organic electronics, such as organic light-emitting diodes (OLEDs), organic eld-effect transistors (OFETs), dye-sensitized solar cells (DSSCs), molecular wires and organic hole-transport layers. [1][2][3] Due to their low reversible oxidation potential they qualify as good donor molecules, and buttery shaped phenothiazines can be easily oxidized to give stable planar colorful radical cations. 4 The optical and electrochemical properties of phenothiazines can be tuned by introducing substituents in 3-and 7-position using cross-coupling reactions, such as Suzuki and Sonogashira coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the venerable electron-rich phenothiazine heterocycles have stimulated increasing scientic interest and have been successfully established in organic electronics, such as organic light-emitting diodes (OLEDs), organic eld-effect transistors (OFETs), dye-sensitized solar cells (DSSCs), molecular wires and organic hole-transport layers. [1][2][3] Due to their low reversible oxidation potential they qualify as good donor molecules, and buttery shaped phenothiazines can be easily oxidized to give stable planar colorful radical cations. 4 The optical and electrochemical properties of phenothiazines can be tuned by introducing substituents in 3-and 7-position using cross-coupling reactions, such as Suzuki and Sonogashira coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has made a fair contribution to the development of bipolar materials for the emissive layer (EML) of OLEDs . By using a reaction scheme consisting of C–C and C–N coupling reactions following classic carbonyl chemistry, we have synthesized pyrroloquinoxaline, , benzothiadiazine-1,1-dioxide, ,, and benzimidazole derivatives as acceptors in π-conjugated bipolar scaffolds. Interestingly, we observed that a rodlike shape of the donor–acceptor (D–A) units in the bipolar molecules proved to be more efficient. , We subsequently synthesized many such molecules with good electroluminescent efficiencies in devices. , The advantages of a rod-shaped design of molecules was twofold.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 We subsequently synthesized many such molecules with good electroluminescent efficiencies in devices. 8,12 The advantages of a rod-shaped design of molecules was twofold. Intrinsically, a linear design of bipolar materials leads to better conjugation and charge transfer between the D−A units.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Benzothiadiazines and their derivatives have been established as versatile pharmacological agents [1] and are prevalent in natural products, pharmaceuticals [2], materials [3], and agricultural chemicals [4]. Many of them are in clinical use and trials.…”
Section: Introductionmentioning
confidence: 99%
“…After the successful preparation of the amino sulfonamide, an appropriate method to cyclize the amine via a C-H sp 3 activation was sought, and a couple of methods were tried to achieve our purpose. The first one was phenyliodine(III) diacetate (PIDA), palladium acetate in the presence of Boc-Ile-OH KOAc, t-BuOH, at 120 C under nitrogen for 24-48 h, which failed to give the required benzothiadiazine [31].…”
Section: Introductionmentioning
confidence: 99%